Planning sustainable tourism in UNESCO wine regions: the case of the Langhe-Roero and Monferrato area - Assumma, Vanessa; Bottero, Marta; Cassatella, Claudia; Cotella, Giancarlo (European Spatial Research and Policy, 2024)
Tourism may be an important leverage for local development. At the same time, it may trigger unwanted effects, ranging from the congestion of services and infrastructures to the progressive deterioration of the assets that they plan to valorise. The article sheds light on this tension, discussing the multiple implications that increasing tourism fluxes generate in the vineyard landscape of Langhe-Roero and Monferrato, included in the UNESCO World Heritage List since 2014. The case study highlights the need to coordinate and enhance coherence among the existing planning and management instruments, towards the consolidation of a multi-level integrated territorial governance framework aimed at the sustainable spatial planning of tourism in the area.